A new analytical technique for the extraction and quantification of microplastics in marine sediments focused on easy implementation and repeatability. Issue 45 (7th November 2017) - Sánchez-Nieva, Julio; Perales, José Antonio; González-Leal, Juan Maria; Rojo-Nieto, Elisa
Abstract : A new analytical approach has been developed to extract and quantify microplastics from sediments, using routine laboratory equipment and NaCl solutions. Abstract : A new analytical approach has been developed to extract and quantify HDPE microparticles from marine sediments. This is the first method that has been proposed using routine laboratory equipment that incorporates slow mixing and air flux for floatation in order to collect the supernatant by overflow, using NaCl saturated solutions. The technique developed in this study comprised the preparation of an HDPE standard of different sizes and calibration curves for artificial enrichment of sediments. Two different techniques were used and compared regarding quantification: (a) stereoscopic microscopy and visual sorting and (b) confocal microscopy and image-processing counting. Microplastics of different sizes were extracted and quantified in sediments with several total concentrations of particles, and different groups of sizes were identified ranging from 0.850 to 0.100 mm. Recoveries exceeding 90% for sediments with higher concentrations of microplastics and above 80% for those with lower concentrations emphasise the potential of this methodology. This is even more remarkable if it is taken into account that different sizes were also used in these experiments. The use of this technique will result not only in a more complete assessment of microplastic concentrations but also in higher repeatability in inter-laboratory comparisons. In addition, this methodology is also suitable for applying the extraction of different polymers of microplastics using other salt solutions such as NaI or ZnCl2 .